2020
DOI: 10.4236/jss.2020.82006
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Harmful Impact of Work Stress on Creativity? Buffering Model of Available Resources

Abstract: How work stress affects creativity has attracted the attention of both enterprises and scholars. Hindrance work stress and Excessive challenge work stress usually impair creativity. However, how to buffer the impairment of work stress on creativity has not been studied in depth. Based on the Job Demands-Resources Model, this study proposes that available resources of employees can buffer the harmful impact of work stress on creativity. Available resources can buffer the negative impact of work stress by supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…A recent meta-analysis found that “change in one or more of the organizational characteristics, namely, physical conditions, job demands, culture, structure or leadership leads to resistance to change by their workforce and development of stress” (Kumar and Pasumarthi, 2019, p. 10). Few researchers have examined the importance of social support in potentially mitigating the negative effects of change, yet research suggests that this important contextual factor impacts many individual work behaviors such as creativity (Liu and Liu, 2020), employee turnover intentions (Gerstner and Day, 1997); citizenship behaviors (Konovsky and Pugh, 1994; Reader et al , 2017); trust levels (Aryee et al , 2002); job satisfaction (Harris et al , 2009) and affective organizational commitment (Eisenberger et al , 2001). Proponents of contextual factors, specifically social exchange theory, consistently “demonstrate the key role that individual-to-individual interactions play in human behavior at work” (Wheeler et al , 2010, p. 183) (See also Cropanzano and Mitchell, 2005).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…A recent meta-analysis found that “change in one or more of the organizational characteristics, namely, physical conditions, job demands, culture, structure or leadership leads to resistance to change by their workforce and development of stress” (Kumar and Pasumarthi, 2019, p. 10). Few researchers have examined the importance of social support in potentially mitigating the negative effects of change, yet research suggests that this important contextual factor impacts many individual work behaviors such as creativity (Liu and Liu, 2020), employee turnover intentions (Gerstner and Day, 1997); citizenship behaviors (Konovsky and Pugh, 1994; Reader et al , 2017); trust levels (Aryee et al , 2002); job satisfaction (Harris et al , 2009) and affective organizational commitment (Eisenberger et al , 2001). Proponents of contextual factors, specifically social exchange theory, consistently “demonstrate the key role that individual-to-individual interactions play in human behavior at work” (Wheeler et al , 2010, p. 183) (See also Cropanzano and Mitchell, 2005).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Existing studies have mainly explained the internal mechanisms underlying the effects of role ambiguity on creativity from the perspectives of destroying intrinsic motivation [ 21 ], consuming individual resources [ 22 ], or developing negative work attitudes [ 11 , 18 ]. However, these explanatory mechanisms are mainly used to explain the harmful effects of role ambiguity and cannot explain the positive relationship between role ambiguity and creativity.…”
Section: Introductionmentioning
confidence: 99%
“…engagement(Song et al,2020), work domain-related factors organizational climate(Liu and Liu 2020), leadership style (Tian et al,2017), and non-work domain-related factors work-family conflict(Choi et al 2018).Innovative work behavior is intentional individual behavior for the introduction and application, in a role, group or organization of ideas, processes, products or procedures, is something new for the unit concerned, designed to significantly benefit individuals, groups, organizations or society wider. The definition of innovative work behavior is the process of generating, introducing and implementing new ideas in order to benefit the organization or group.…”
mentioning
confidence: 99%